2010
DOI: 10.1111/j.1365-2222.2010.03625.x
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the field of allergy in 2009 through the eyes of Clinical and Experimental Allergy

Abstract: In 2009 the journal published in the region of 200 papers including reviews, editorials, opinion pieces and original papers that ran the full gamut of allergic disease. It is instructive to take stock of this output to determine patterns of interest and where the cutting edge lies. We have surveyed the field of allergic disease as seen through the pages of Clinical and Experimental Allergy (CEA) highlighting trends, emphasizing notable observations and placing discoveries in the context of other key papers pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 183 publications
(220 reference statements)
1
0
0
Order By: Relevance
“…In industrial nations, a steady rise in sensitization has been observed since the 1920s, with a strong increase in the 1990s. Up to 11% of the US population suffer from allergic rhinitis, 3% from asthma and 6% from food allergies [4,5]. Similar data are reported from the UK and Europe.…”
Section: Introductionsupporting
confidence: 70%
“…In industrial nations, a steady rise in sensitization has been observed since the 1920s, with a strong increase in the 1990s. Up to 11% of the US population suffer from allergic rhinitis, 3% from asthma and 6% from food allergies [4,5]. Similar data are reported from the UK and Europe.…”
Section: Introductionsupporting
confidence: 70%